Ownership as a Form of Corporate Governance - Connelly, Brian L.; Hoskisson, Robert E.; Tihanyi, Laszlo; Certo, S. Trevis (Journal of Management Studies, 2010)
abstractFirm ownership is an increasingly influential form of corporate governance. Although firms might be owned by different types of owners, most studies examine owner influence on a particular firm outcome in isolation. This study synthesizes research from multiple disciplines on different types of owners and offers a unifying framework of governance through ownership. Using this framework, we describe the motivations of various types of owners, the tactics owners use to affect firms in which they are invested, and the dominant firm outcomes these owners seek to influence. We note how heightened managerial awareness of heterogeneous owner interests increases owner influence on firm‐level outcomes. We also provide a roadmap for future study and offer research questions about where scholars might turn their attention to better understand the role of owners in directing firm actions. Our study draws attention to emerging forms of ownership, such as hedge funds and sovereign wealth funds, and highlights the changing (and often competing) interests of shareholders and how this impacts theories of governance.